Ways to improve biogeneity, assimilation potential and fertility of soil cover of the urban landscapes of Sumgait city - S. I. Nadjafova; Ch. Z. Bagirova (Юг России: экология, развитие)
Aim. The aim of the research was to identify the possibility of increasing the content of humus in the soil cover of the city of Sumgait using biologics, including those containing cellulose‐decomposing microorganisms, in a controlled manner.Material and Methods. In the process of conducting laboratory experiments, we took soil samples with the introduction of various modifications of organic substances of plant origin and with the simultaneous introduction of biologics. As biopreparations, we used cultures of cellulose‐decomposing microorganisms isolated from soils, excess activated sludge and the Fermi‐Start biopreparation, both individually and in the form of compositions. Total carbon content was carried out according to the Tyurin method. The total number of microorganisms was determined by generally accepted methods. Enzyme activity was determined by the F. Kh. Khaziev method.Results. It was revealed that the use of biopreparations – the association of cellulose‐decomposing bacteria, excess activated sludge and Fermi‐Start stimulated an increase in the number of cellulose‐decomposing bacteria (3‐10 times) and the accumulation of total carbon and humus in the soil by 20‐55%.Conclusion. The use of biological preparations and the introduction of cellulose‐containing materials into the soil, provided that optimum moisture is maintained, ensures in a short period of time – 6 months ‐ a significant increase of humus in the gray‐brown soil content.